The metabotropic glutamate receptor subtype 1 regulates development and maintenance of lemniscal synaptic connectivity in the somatosensory thalamus. - Madoka Narushima; Yuki Yagasaki; Yuichi Takeuchi; Atsu Aiba; Mariko Miyata (PLoS ONE, 2019)
The metabotropic glutamate receptor subtype 1 (mGluR1) is a major subtype of group I mGluRs, which contributes to the development and plasticity of synapses in the brain. In the sensory thalamus, the thalamocortical neuron receives sensory afferents and massive feedback input from corticothalamic (CT) fibers. Notably, mGluR1 is more concentrated in CT synapses in the sensory thalamus. In the visual thalamus, mGluR1 maintains mature afferent synaptic connectivity. However, it is unknown whether mGluR1 contributes to strengthening of immature synapses or weakening of excess synapses during development and whether mGluR1 at CT synapses heterosynaptically regulates the development or refinement of afferent synapses. Here we investigated the effects of knocking out the gene encoding mGluR1 or pharmacologically blocking cortical activity on the development and maintenance of lemniscal synapses, i.e., the somatosensory afferent synapses, in the ventral posteromedial somatosensory thalamus. mGluR1-knockout (KO) mice exhibited delayed developmental strengthening as well as incomplete elimination and remodeling after maturation of lemniscal synapses. Similar to the phenotypes exhibited by mGluR1-KO mice, pharmacological blockade of somatosensory cortical activity from P12 or P21 for 1 week in wild-type mice perturbed elimination or maintenance of lemniscal synapses, respectively. The same manipulation in mGluR1-KO mice failed to induce additional abnormalities in lemniscal synaptic connectivity. These results suggest that activation of mGluR1, driven by CT input, regulates multiple stages of the development of lemniscal synapses, including strengthening, refinement, and maintenance in the somatosensory thalamus.